Right Ventricle to Pulmonary Artery Coupling Predicts the Risk Stratification in Patients With Systemic Sclerosis-Associated Pulmonary Arterial Hypertension - Lai, Jinzhi; Zhao, Jiuliang; Li, Kaiwen; Qin, Xiaohan; Wang, Hui; Tian, Zhuang; Wang, Qian; Li, Mengtao; Guo, Xiaoxiao; Liu, Yongtai; Zeng, Xiaofeng (Frontiers in Cardiovascular Medicine, 2022)
Background: Pulmonary arterial hypertension (PAH) is a serious complication of systemic sclerosis (SSc). PAH has high mortality, and risk assessment is critical for proper management. Whether the right ventricle to pulmonary artery (RV-PA) coupling accurately assesses risk status and predicts prognosis in patients with SSc-associated PAH has not been investigated. Methods: Between March 2010 and July 2018, 60 consecutive patients with SSc-associated PAH diagnosed by right heart catheterization were enrolled prospectively, and the mean follow-up period was 52.9 ± 27.0 months. The RV-PA coupling was assessed by the ratio of tricuspid annular plane systolic excursion (TAPSE) and pulmonary artery systolic pressure (PASP) which was obtained by transthoracic echocardiography. The simplified risk stratification strategy was applied to assess the risk level of participants, and the endpoint was a composite of all-cause death and clinical worsening. Results: The receiver operating characteristic (ROC) curve of the ability to determine high-risk patients identified the optimal cut-off value of the TAPSE/PASP ratio as 0.194 mm/mmHg, and the ratio appeared to be a reliable indicator in the stratification of patients with high risk (area under the curve = 0.878, ROC P-value = 0.003), which showed the highest positive likelihood ratio (LR) (5.4) and the lowest negative LR (0) among a series of echocardiographic parameters. The TAPSE/PASP ratio was an independent predictive factor (HR=0.01, 95% CI 0.00-0.77, P=0.037) for the composite endpoint, and patients with a TAPSE/PASP ratio > 0.194 had a better overall survival for both the composite endpoint (log-rank χ = 5.961, P = 0.015) and all-cause mortality (log-rank χ = 8.004, P = 0.005) compared to the patients with a TAPSE/PASP ≤ 0.194. Conclusions: RV-PA coupling assessed by the TAPSE/PASP ratio provides added value as a straightforward and non-invasive approach for predicting risk stratification of patients with SSc-associated PAH. Meanwhile, a lower TAPSE/PASP ratio identified a subgroup with worse prognosis.